Controllable tomography phase microscopy. (March 2015) - Xiu, Peng; Zhou, Xin; Kuang, Cuifang; Xu, Yingke; Liu, Xu
Abstract: Tomography phase microscopy (TPM) is a new microscopic method that can quantitatively yield the volumetric 3D distribution of a sample׳s refractive index (RI), which is significant for cell biology research. In this paper, a controllable TPM system is introduced. In this system a circulatory phase-shifting method and piezoelectric ceramic are used which enable the TPM system to record the 3D RI distribution at a more controllable speed, from 1 to 40 fps, than in the other TPM systems reported. The resolution of the RI distribution obtained by this controllable TPM is much better than that in images recorded by phase contrast microscopy and interference tomography microscopy. The realization of controllable TPM not only allows for the application of TPM to the measurement of kinds of RI sample, but also contributes to academic and technological support for the practical use of TPM.